Health care and societal costs of the management of children and adolescents with attention-deficit/hyperactivity disorder in Spain: a descriptive analysis - Quintero, Javier; Ramos-Quiroga, Josep A.; Sebastián, Javier San; Montañés, Francisco; Fernández-Jaén, Alberto; Martínez-Raga, José; Giral, Marta García; Graell, Montserrat; Mardomingo, María J.; Soutullo, César; Eiris, Jesús; Téllez, Montserrat; et al. (BMC psychiatry, 2018)
Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental condition in childhood (5.3% to 7.1% worldwide prevalence), with substantial overall financial burden to children/adolescents, their families, and society. The aims of this study were to describe the clinical characteristics of children and adolescents with ADHD in Spain, estimate the associated direct/indirect costs of the disorder, and assess whether the characteristics and financial costs differed between children/adolescents adequately responding to currently available pharmacotherapies compared with children/adolescents for whom pharmacotherapies failed. This was a multicenter, cross-sectional, descriptive analysis conducted in 15 health units representative of the overall Spanish population. Data on demographic characteristics, socio-occupational status, social relationships, clinical variables of the disease, and pharmacological and non-pharmacological treatments received were collected in 321 children and adolescents with ADHD. Direct and indirect costs were estimated over one year from both a health care system and a societal perspective. The estimated average cost of ADHD per year per child/adolescent was €5733 in 2012 prices; direct costs accounted for 60.2% of the total costs (€3450). Support from a psychologist/educational psychologist represented 45.2% of direct costs and 27.2% of total costs. Pharmacotherapy accounted for 25.8% of direct costs and 15.5% of total costs. Among indirect costs (€2283), 65.2% was due to caregiver expenses. The total annual costs were significantly higher for children/adolescents who responded poorly to pharmacological treatment (€7654 versus €5517; P = 0.024), the difference being mainly due to significantly higher direct costs, particularly with larger expenses for non-pharmacological treatment (P = 0.012). ADHD has a significant personal, familial, and financial impact on the Spanish health system and society. Successful pharmacological intervention was associated with lower overall expenses in the management of the disorder.